Electrochemical device and electronic device
By adjusting the strength of the negative electrode current collector, the uniform distribution of silicon in the silicon-based particles, the silicon content in the negative electrode material layer, and the electrolyte composition, the distribution of silicon-based composite materials of the lithium-ion battery is optimized, and the problems of cycling and expansion performance of the lithium-ion battery are solved, achieving a comprehensive improvement of battery performance.
Patent Information
- Application Number
- CN202411921459.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-12-27
AI Technical Summary
During the circulation process, the volume expansion and contraction of the silicon material lead to repeated damage to the solid electrolyte interface film, affecting its circulation and expansion performance.
By synergistically adjusting the strength A of the negative electrode current collector, the fluctuation value of the relative percentage content of silicon atoms in the silicon-based particles, the mass content C of the silicon element in the negative electrode material layer, the porosity P of the negative electrode sheet and the fluorovinyl carbonate content Q in the electrolyte, the distribution of the silicon-based composite material and the composition of the electrolyte are optimized to improve the circulation and expansion performance of the lithium-ion battery.
It achieves good circulation and expansion performance of lithium-ion batteries, extends the service life of the battery, and balances the energy density and production costs of the battery.
Smart Images

Figure CN119725684A_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application submitted to the China Patent Office on December 27, 2021, with application number 202180030502.7 and invention name “An electrochemical device and electronic device”. Technical Field
[0002] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device. Background Art
[0003] Lithium-ion batteries have many advantages, such as high volume and mass energy density, long cycle life, high nominal voltage, low self-discharge rate, small size, and light weight, and are widely used in the field of consumer electronics. With the rapid development of electric vehicles and mobile electronic devices in recent years, people have higher and higher demands on battery energy density, safety, cycle performance, etc., and look forward to the emergence of new lithium-ion batteries with comprehensive performance improvements.
[0004] Silicon materials have high specific capacity and can significantly improve the energy density of lithium-ion batteries as negative electrode materials. However, they have large volume expansion and contraction during the process of lithium insertion and extraction, which causes repeated destruction and generation of the solid electrolyte interface (SEI) during the cycle, consumes reversible lithium, and affects the cycle performance and expansion performance of lithium-ion batteries. Summary of the invention
[0005] The purpose of this application is to provide an electrochemical device and an electronic device to improve the cycle performance and expansion performance of lithium-ion batteries. The specific technical solution is as follows:
[0006] The first aspect of the present application provides an electrochemical device, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer, wherein the negative electrode material layer comprises a silicon-based composite material, the silicon-based composite material comprises silicon-based particles, the strength of the negative electrode current collector is A MPa, the difference between the maximum and minimum values of the relative percentage content of silicon atoms in the silicon-based particles is B%, and the mass content of silicon element in the negative electrode material layer is C%, satisfying:
[0007]
[0008] The present application achieves a lithium-ion battery with good cycle performance and expansion performance by synergistically adjusting A, B, and C to meet the above conditions.
[0009] In one embodiment of the present application, B satisfies: 10≤B≤16. By adjusting B within the above range, silicon-based particles with good uniformity of silicon element distribution can be obtained, which is beneficial to reduce the stress generated by the expansion of the lithium ion battery, thereby obtaining a lithium ion battery with good cycle performance and expansion performance.
[0010] In one embodiment of the present application, C satisfies: 1≤C≤20. By adjusting C within the above range, the expansion performance and energy density of the lithium-ion battery can be balanced.
[0011] In one embodiment of the present application, A satisfies: 370≤A≤800. By adjusting A within the above range, it is beneficial to balance the expansion performance and production cost of the lithium-ion battery.
[0012] In one embodiment of the present application, the thickness of the negative electrode material layer on one side is H, the maximum particle size of the silicon-based particles is Dmax, and H≥3×Dmax is satisfied. By adjusting H and Dmax to satisfy the above relationship, the cycle performance and expansion performance of the lithium-ion battery can be improved.
[0013] In one embodiment of the present application, the Dmax of the silicon-based particles satisfies: 10 μm ≤ Dmax ≤ 25 μm. By adjusting Dmax within the above range, it is beneficial to balance the processing performance, expansion performance and energy density of the lithium-ion battery.
[0014] In one embodiment of the present application, the single-sided thickness H of the negative electrode material layer satisfies: 30 μm ≤ H ≤ 90 μm. By adjusting the single-sided thickness H of the negative electrode material layer within the above range, the strength and toughness of the negative electrode material layer can be balanced, thereby improving the performance of the lithium-ion battery.
[0015] In one embodiment of the present application, the porosity of the negative electrode sheet is P%, wherein P and C satisfy: P>15×C 1 / 4 By adjusting P and C to satisfy the above relationship, the expansion performance and kinetic performance of lithium-ion batteries are improved.
[0016] In one embodiment of the present application, P satisfies: 18≤P≤40. By adjusting P within the above range, the negative electrode plate can be effectively infiltrated in the electrolyte, and the negative electrode plate has good strength, thereby improving the expansion performance and dynamic performance of the lithium-ion battery.
[0017] In one embodiment of the present application, the electrolyte includes fluoroethylene carbonate, and the mass percentage of the fluoroethylene carbonate is Q% based on the mass of the electrolyte, and Q and C satisfy: 0.3≤C / Q≤3. By adjusting Q and C to satisfy the above relationship, a lithium-ion battery with good expansion performance and dynamic performance can be obtained.
[0018] In one embodiment of the present application, Q satisfies: 1≤Q≤20. By adjusting Q within the above range, the cycle performance of the lithium-ion battery is improved.
[0019] In one embodiment of the present application, the silicon-based particles include silicon and carbon, and the atomic ratio of silicon to carbon in the silicon-based particles is 1:1 to 2.5. The negative electrode sheet of the present application includes silicon-based particles having the above-mentioned atomic ratio of elements, and a lithium-ion battery with good expansion performance and cycle performance can be obtained.
[0020] A second aspect of the present application provides an electronic device, which includes the electrochemical device described in the first aspect.
[0021] The present application provides an electrochemical device and an electronic device, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, the negative electrode sheet comprising a negative electrode current collector and a negative electrode material layer, the negative electrode material layer comprising a silicon-based composite material, the silicon-based composite material comprising silicon-based particles, the strength of the negative electrode current collector is A MPa, the difference between the maximum value and the minimum value of the relative percentage content of silicon atoms in the silicon-based particles is B%, the mass content of silicon element in the negative electrode material layer is C%, and the following conditions are satisfied:
[0022]
[0023] By adjusting A, B, and C in coordination to meet the above conditions, the obtained lithium-ion battery has good cycle performance and expansion performance. Of course, it is not necessary to achieve all the advantages described above at the same time when implementing any embodiment of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the present application and the prior art, the following briefly introduces the drawings required for use in the embodiments and the prior art. Obviously, the drawings described below are only some embodiments of the present application.
[0025] Figure 1a is a scanning electron microscope (SEM) image of a cross section of a silicon-based particle;
[0026] Figure 1b It is the fluctuation curve of the relative percentage content of silicon atoms in the X-ray energy dispersive spectrometer (EDS) line scan. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme, and advantages of the present application more clearly understood, the present application is further described in detail with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other technical schemes obtained by ordinary technicians in the field belong to the scope of protection of the present application.
[0028] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0029] In the prior art, in order to improve the lithium insertion expansion problem of silicon negative electrode, it is mainly achieved through silicon nano-sizing and composite. For example, by reducing the particle size of silicon material to nanometer level, the stress generated when it is inserted into lithium is relieved, and the cracking of the material is reduced; or by compounding with other carbonaceous materials, its contact with the electrolyte is reduced, and the generation of solid electrolyte interface (SEI) is reduced. However, the silicon nano-sizing method has the problems of complex preparation process and high energy consumption, and the excessively high specific surface area of nano silicon material makes it extremely easy to agglomerate, which affects the electrical performance of lithium-ion batteries; the existing composite method is limited to improving the expansion performance and cycle performance of lithium-ion batteries because it only improves carbonaceous composite materials and ignores the overall influence of other factors on the expansion of lithium-ion batteries. In addition, the volume expansion caused by lithium insertion is an intrinsic property of silicon-based materials. Although relying solely on these solutions can improve the expansion of silicon negative electrodes to a certain extent, it is not enough to meet the application of industrial products.
[0030] In view of this, the present application provides an electrochemical device and an electronic device to improve the cycle performance and expansion performance of a lithium-ion battery.
[0031] The first aspect of the present application provides an electrochemical device, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer, wherein the negative electrode material layer comprises a silicon-based composite material, the silicon-based composite material comprises silicon-based particles, the strength of the negative electrode current collector is A MPa, the difference between the maximum and minimum values of the relative percentage content of silicon atoms in the silicon-based particles is B%, the mass content of silicon element in the negative electrode material layer is C%, and the following conditions are satisfied:
[0032]
[0033] The inventors of this application have found that the difference B% between the maximum and minimum values of the relative percentage content of silicon atoms in silicon-based particles is a fluctuation value, which can represent the uniformity of the distribution of silicon elements in silicon-based particles. The larger the fluctuation value, the worse the uniformity of the distribution of silicon elements. Volume expansion will occur during the lithium insertion process of silicon, and the expansion will occur in multiple directions (for example, along the length, width and height directions of the lithium-ion battery). Therefore, the negative electrode collector needs to have a certain strength to resist the stress caused by the expansion, thereby inhibiting the deformation of the lithium-ion battery. The inventors of this application also found that the more uniform the distribution of silicon elements inside the silicon-based particles, the smaller the stress caused by the expansion; the more silicon elements in the negative electrode material layer, the greater the expansion trend during the cycle of the lithium-ion battery; as the fluctuation degree of the silicon element distribution in the silicon-based particles and the mass content of the silicon element in the negative electrode material layer increase, the demand for the strength of the negative electrode collector is higher, but when the negative electrode collector exceeds a certain strength, the degree of improvement in the cycle and expansion performance will be greatly reduced. Based on the above findings, the present application can obtain a lithium-ion battery with good cycle performance and expansion performance by synergistically adjusting A, B, and C to meet the above conditions.
[0034] In one embodiment of the present application, B satisfies: 10≤B≤16. By adjusting B within the above range, silicon-based particles with good uniformity of silicon element distribution can be obtained, which is beneficial to reduce the stress generated by the expansion of the lithium ion battery, thereby obtaining a lithium ion battery with good cycle performance and expansion performance.
[0035] In one embodiment of the present application, C satisfies: 1≤C≤20. By adjusting C within the above range, the following situations can be avoided: too little silicon in the negative electrode material layer may affect the energy density of the lithium-ion battery; too much silicon in the negative electrode material layer may aggravate the expansion trend of the lithium-ion battery. Therefore, by adjusting C within the above range, it is beneficial to balance the energy density and expansion performance of the lithium-ion battery.
[0036] In one embodiment of the present application, A satisfies: 370≤A≤800. By adjusting A within the above range, the following situations can be avoided: the strength of the negative electrode current collector is too low, affecting the expansion performance of the lithium-ion battery; the strength of the negative electrode current collector is too high, which does not improve the cycle and expansion performance on the one hand, and greatly increases the production cost of the current collector on the other hand. Therefore, by adjusting A within the above range, it is beneficial to balance the expansion performance and production cost of the lithium-ion battery.
[0037] In one embodiment of the present application, the single-sided thickness of the negative electrode material layer is H, and the maximum particle size of the silicon-based particles is Dmax, satisfying: H≥3×Dmax. By adjusting the relationship between H and Dmax to satisfy the above relationship, the cycle performance and expansion performance of the lithium-ion battery can be improved. It is speculated that this may be due to the large expansion of the silicon material when lithium is embedded. When the thickness of the negative electrode pole piece is constant, the Dmax of the silicon-based particles is too large, which can easily lead to uneven expansion of the pole piece, causing excessive local expansion of the negative electrode pole piece. In addition, since the dispersion process of the negative electrode material slurry is not an ideal situation of completely uniform dispersion, some silicon-based particles may be unevenly dispersed in the negative electrode pole piece. If the Dmax of the silicon-based particles is too large, it is easy to cause convex points on the negative electrode pole piece, affecting the appearance and performance of the negative electrode pole piece, thereby affecting the cycle performance and expansion performance of lithium ions. Therefore, by adjusting the relationship between H and Dmax to satisfy the above relationship, a lithium-ion battery with good cycle performance and expansion performance can be obtained.
[0038] It is understandable that the negative electrode material layer can be provided on a single side of the negative electrode current collector, i.e., single-sided coating, or can be provided on both sides of the negative electrode current collector, i.e., double-sided coating. In one example, assuming that the overall thickness of the negative electrode sheet is h and the thickness of the negative electrode current collector is h1, when double-sided coating is used, H is: H = (h-h1) / 2; when single-sided coating is used, H is: H = h-h1.
[0039] In one embodiment of the present application, the Dmax of the silicon-based particles satisfies: 10μm≤Dmax≤25μm. By adjusting Dmax within the above range, the following situations can be avoided: if the Dmax of the silicon-based particles is too large, it is easy to cause uneven expansion of the pole piece, and it is easy to produce convex point problems during the processing, affecting the interface and expansion performance of the lithium-ion battery; if the Dmax of the silicon-based particles is too small, the specific surface area is too large, and more SEI film is accumulated on the surface of the negative electrode, increasing the expansion trend, and more binders are required during the processing to achieve the bonding effect, reducing the energy density of the lithium-ion battery. Therefore, the present application is conducive to balancing the processing performance, expansion performance and energy density of lithium-ion batteries by adjusting Dmax within the above range.
[0040] In one embodiment of the present application, the single-sided thickness H of the negative electrode material layer satisfies: 30 μm ≤ H ≤ 90 μm. By adjusting the single-sided thickness H of the negative electrode material layer within the above range, the strength and toughness of the negative electrode material layer can be balanced, thereby improving the performance of the lithium-ion battery.
[0041] In one embodiment of the present application, the porosity of the negative electrode sheet is P%, wherein P and C satisfy: P>15×C 1 / 4. By adjusting P and C to satisfy the above relationship, the expansion performance and kinetic performance of lithium-ion batteries are improved. It is speculated that this may be due to the fact that the volume expansion of silicon-based materials is very large (about 300%) after lithium is embedded. The huge volume effect easily leads to problems such as demolding and powder loss of the negative electrode sheets. Negative electrode sheets with a certain porosity can effectively alleviate the volume expansion of silicon-based materials. However, when the porosity of the negative electrode sheet is too low, it is difficult for the electrolyte to fully infiltrate the negative electrode sheet, increase the transmission distance of lithium ions, and affect the kinetic performance of the lithium-ion battery. Therefore, by adjusting P and C to satisfy the above relationship, a lithium-ion battery with good expansion performance and kinetic performance can be obtained.
[0042] In one embodiment of the present application, P satisfies: 18≤P≤40. By adjusting P within the above range, the negative electrode plate can be effectively wetted in the electrolyte, and the negative electrode plate has good strength, thereby improving the expansion performance and dynamic performance of the lithium-ion battery.
[0043] In one embodiment of the present application, the electrolyte includes fluoroethylene carbonate (FEC), and the mass percentage of fluoroethylene carbonate is Q% based on the mass of the electrolyte, and Q and C satisfy: 0.3≤C / Q≤3. By adjusting Q and C to satisfy the above relationship, the following situations can be avoided: when C / Q is too high, the expansion tendency of the lithium-ion battery during the cycle process increases, and when C / Q is too low, the addition of FEC will reduce the mobility of lithium ions in the electrolyte, affecting the rate performance of the lithium-ion battery. Therefore, by adjusting Q and C to satisfy the above relationship, a lithium-ion battery with good expansion performance and dynamic performance can be obtained.
[0044] In one embodiment of the present application, Q satisfies: 1≤Q≤20. Fluoroethylene carbonate (FEC) is an important film-forming additive in the electrolyte. The SEI film generated by its decomposition during the cycle of the lithium-ion battery further contacts the electrolyte and reduces the consumption of lithium ions. By adjusting Q within the above range, it is beneficial to improve the cycle performance of the lithium-ion battery.
[0045] In one embodiment of the present application, the silicon-based particles include silicon and carbon, and the atomic ratio of silicon to carbon in the silicon-based particles is 1:1 to 2.5. The negative electrode sheet of the present application includes silicon-based particles having the above-mentioned atomic ratio of elements, and a lithium-ion battery with good expansion performance and cycle performance can be obtained.
[0046] The present application has no restrictions on the preparation method of the silicon-based composite material, as long as the purpose of the present application can be achieved. For example, an organic substance is carbonized to obtain a porous carbon matrix, and then the porous carbon matrix is placed in a silicon-containing gas atmosphere, and then heat-treated to obtain a silicon-based composite material. In one example, the following preparation method can be used:
[0047] The porous carbon matrix is placed in a rotary kiln, the furnace tube is purged with nitrogen at room temperature for 20 to 40 minutes, and then the temperature of the porous carbon matrix sample is increased to 450°C to 500°C. The nitrogen flow rate is adjusted so that the residence time of the gas in the rotary kiln is at least 90 seconds, and the flow rate is maintained for about 30 minutes. The gas supply is then switched from nitrogen to a mixed gas of silicon-containing gas and nitrogen (the volume fraction of silicon-containing gas in the mixed gas is 5% to 30%). After deposition for 8 to 16 hours at a gas flow rate of 200sccm to 400sccm, nitrogen is continuously passed into the rotary kiln to blow out the silicon-containing gas from the furnace, and then the rotary kiln is purged for 30 minutes under nitrogen conditions, and then the rotary kiln is cooled to room temperature within 5 to 10 hours. Then, by converting the airflow from nitrogen to air from a compressed air source, the nitrogen in the rotary kiln is gradually converted to air within 1 to 2 hours to obtain a silicon-based composite material.
[0048] In the present application, the type of porous carbon matrix is not particularly limited, as long as the purpose of the present application can be achieved. For example, the porous carbon matrix can be selected from at least one of hard carbon, soft carbon, and graphite. Exemplarily, the hard carbon can include resin carbon, carbon black, organic polymer pyrolytic carbon, and combinations thereof. The soft carbon can include carbon fibers, carbon microspheres, and combinations thereof. The particle size of the porous carbon matrix is not limited, as long as the purpose of the present application can be achieved. For example, the particle size range of the porous carbon matrix is 3 μm. <Dv50<15μm,15μm<Dv99<30μm。
[0049] The difference B% between the maximum and minimum values of the relative percentage content of silicon atoms in the silicon-based particles is related to the uniformity of the pore distribution inside the carbon matrix and the pore size. For example, the more uniform the pore distribution inside the carbon matrix, the smaller the B%. Based on this, the B% can be adjusted by adjusting the pore distribution and pore size.
[0050] The mass content C% of silicon in the negative electrode material layer is related to the amount of silicon-based composite material added, wherein the silicon content deposited inside the silicon-based composite material can be adjusted by adjusting the deposition temperature, deposition time, and the concentration of silicon-containing gas used. For example, C% usually increases with the increase of deposition temperature, C% usually increases with the increase of deposition time, and C% usually increases with the increase of silicon-containing gas concentration. Based on this, the mass content C% of silicon in the negative electrode material layer can be adjusted.
[0051] The maximum particle size Dmax of the silicon-based particles is positively correlated with the particle size of the porous carbon matrix. Based on this, the maximum particle size Dmax of the silicon-based particles can be adjusted by screening the porous carbon matrix.
[0052] The porosity of the negative electrode sheet usually decreases as the compaction density of the negative electrode sheet increases. Based on this, the porosity of the negative electrode sheet can be adjusted by adjusting the cold pressing pressure of the negative electrode sheet and adjusting the compaction density of the negative electrode sheet.
[0053] The atomic ratio of silicon to carbon in the silicon-based particles can be adjusted by adjusting the ratio of silicon-containing gas to nitrogen in the mixed gas. Generally, as the ratio of silicon-containing gas in the mixed gas increases, more silicon will be deposited in the porous carbon matrix, increasing the atomic ratio of silicon to carbon in the silicon-based particles.
[0054] In the present application, the negative electrode sheet includes a negative electrode current collector, and the negative electrode material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the negative electrode current collector, as long as the purpose of this application can be achieved. For example, it can include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or composite current collector. In the present application, there is no special restriction on the thickness of the negative electrode current collector, as long as the purpose of this application can be achieved, for example, the thickness is 4μm to 12μm. The thickness of the negative electrode material layer of this application can be 70μm to 120μm.
[0055] In the present application, the negative electrode material layer may include, in addition to the above-mentioned silicon-based composite material, other negative electrode active materials known in the art, for example, including but not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel-structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.
[0056] In the present application, the negative electrode material layer may also include a negative electrode conductive agent. The present application has no particular restrictions on the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of a carbon-based material, a metal-based material or a conductive polymer. The above-mentioned carbon-based material is selected from at least one of natural graphite, artificial graphite, conductive carbon black, acetylene black, Ketjen black or carbon fiber. The above-mentioned metal-based material may include but is not limited to metal powder and / or metal fiber. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.
[0057] In the present application, the negative electrode material layer may also include a negative electrode binder. The present application has no particular limitation on the negative electrode binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyacrylic acid, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or at least one of nylon.
[0058] Optionally, the negative electrode sheet may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art, and may include but is not limited to the above-mentioned negative electrode conductive agent and the above-mentioned negative electrode binder.
[0059] The electrolyte of the present application may also include lithium salts and other non-aqueous solvents. The present application has no particular restrictions on the lithium salts, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB or lithium difluoroborate. Preferably, the lithium salt includes LiPF6.
[0060] The present application has no particular restrictions on other non-aqueous solvents, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of linear carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The above-mentioned cyclic carbonate may include but is not limited to at least one of butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The content of the other non-aqueous solvents is not particularly limited, as long as the purpose of the present application can be achieved. For example, the mass percentage of the above-mentioned other non-aqueous solvents is 67% to 87%, for example, 67%, 67.5%, 70%, 75%, 80%, 83%, 85%, 86.5%, 87% or any range therebetween.
[0061] The electrochemical device of the present application may also include a positive electrode sheet. The present application has no special restrictions on the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet usually includes a positive current collector and a positive electrode material layer. The positive electrode material layer can be arranged on one surface in the thickness direction of the positive current collector, or on two surfaces in the thickness direction of the positive current collector. It should be noted that the "surface" here can be the entire area of the positive current collector, or it can be a partial area of the positive current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved. In the present application, there is no special restriction on the positive current collector, as long as the purpose of the present application can be achieved, for example, it can include but is not limited to aluminum foil, aluminum alloy foil or composite current collector. In the present application, there is no special restriction on the thickness of the positive current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 8μm to 12μm.
[0062] In the present application, the positive electrode material layer includes a positive electrode active material. The present application has no particular restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved, for example, it may include at least one of lithium or a composite oxide of a transition metal element. The present application has no particular restrictions on the above-mentioned transition metal elements, as long as the purpose of the present application can be achieved, for example, it may include at least one of nickel, manganese, cobalt or iron. Specifically, the positive electrode active material may include at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.
[0063] In the present application, the positive electrode material layer may also include a positive electrode conductive agent. The present application has no particular restrictions on the positive electrode conductive agent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, acetylene black, flake graphite, Ketjen black, graphene, metal materials or conductive polymers. Preferably, the positive electrode conductive agent includes conductive carbon black and carbon nanotubes. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but are not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. In the present application, the positive electrode material layer may also include a positive electrode binder. The present application has no particular limitation on the positive electrode binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of fluorine-containing resins, polypropylene resins, fiber-type binders, rubber-type binders or polyimide-type binders.
[0064] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a conductive layer commonly used in the art, for example, including but not limited to the above-mentioned positive electrode conductor and the above-mentioned positive electrode binder.
[0065] The electrochemical device of the present application may also include a separator. The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. The above-mentioned separator may include a substrate layer and a surface treatment layer. The present application has no particular restrictions on the substrate layer. For example, it may include but is not limited to polyethylene, polypropylene, polytetrafluoroethylene-based polyolefin separators, polyester films (such as polyethylene terephthalate films), cellulose films, polyimide films, polyamide films, spandex, aramid films, woven films, non-woven films (non-woven fabrics), microporous films, composite films, separator paper, rolled films or spinning films. At least one of them is preferably polyethylene or polypropylene, which has a good effect on preventing short circuits and can improve the stability of electrochemical devices through the shutdown effect. The separator of the present application may have a porous structure, and the size of the pore size is not particularly limited, as long as the purpose of the present application can be achieved. For example, the size of the pore size can be 0.01 μm to 1 μm. In the present application, the thickness of the separator is not particularly limited, as long as the purpose of the present application can be achieved, for example, the thickness can be 5 μm to 500 μm.
[0066] In the present application, a surface treatment layer is provided on at least one surface of the above-mentioned substrate layer. The present application has no particular restrictions on the surface treatment layer, which may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer may include, but is not limited to, inorganic particles and inorganic layer binders. The present application has no particular restrictions on inorganic particles, for example, it may include, but is not limited to, at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the inorganic layer binder, for example, it may include, but is not limited to, at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The polymer layer contains a polymer. The present application has no particular limitation on the polymer. The material of the polymer may include but is not limited to at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).
[0067] The electrochemical device of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In some embodiments, the electrochemical device may include, but is not limited to, a lithium-ion battery.
[0068] The preparation process of the electrochemical device is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a wound structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device; or stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0069] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electrochemical device provided by the present application has good expansion performance and cycle performance, so that the electronic device provided by the present application has a long service life.
[0070] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0071] Example
[0072] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0073] Test methods and equipment:
[0074] Negative electrode porosity test:
[0075] The porosity of the negative electrode sheet was tested by the gas replacement method: 50 negative electrode sheets with a radius of d were punched out using the same mold, the thickness h of each negative electrode sheet was measured, and the 50 negative electrode sheets were placed in the sample cup of the test equipment (AccuPycП1340), and the negative electrode sheets were filled with helium in the closed sample chamber, thereby measuring the true volume V of the negative electrode sheet, and then the porosity of the negative electrode sheet was calculated by the following formula: P = (1-V / πd 2 ×50×h)×100%.
[0076] Current collector strength test:
[0077] The current collector is punched out into a test sample with a width of 15 mm and a length of 70 mm using a punching machine. The sample is fixed to the test fixture of the high-speed rail tensile machine to test the tensile strength of the sample. The tensile speed is 5 mm / min, and the standard distance between the two fixtures of the tensile machine is 50 mm. The tensile strength and displacement curves are recorded, and the tensile strength sudden drop point is the strength to resist external force damage.
[0078] Test of silicon content in negative electrode material layer:
[0079] The negative electrode plate was dried in a vacuum oven at 100°C for 24 hours, part of the active material on the negative electrode plate was scraped off with a blade and weighed to obtain a mass M1, and the scraped active material was then heat treated at 800°C in a continuous air atmosphere to remove the carbonaceous material. The remaining material was weighed to obtain a mass M2, and then the silicon content in the negative electrode material layer was calculated using the following formula: C = 0.467M2 / M1×100%.
[0080] Determination of the difference between the maximum and minimum values of the relative percentage content of silicon atoms in silicon-based particles:
[0081] The negative electrode was placed in a vacuum oven at 100°C and dried for 24 hours. In a protective atmosphere (such as nitrogen), the silicon-based particles in the electrode were processed into thin sheets of 50nm to 100nm using a focused ion beam (FIB). The SEM image is shown in Figure 2. Figure 1a Then, the relative percentage of silicon atoms in the silicon-based particles was tested by line scanning using an X-ray energy dispersive spectrometer (EDS) in a transmission electron microscope (TEM). The test results are shown in Table 1. Figure 1b The line scan position is selected at any position inside the silicon-based particle, for example, Figure 1b The starting and ending points of the line scan data correspond to Figure 1a The starting and ending points of the black arrow line are Figure 1b The line scan data is Figure 1a The data corresponding to the position where the black arrow line passes. The fluctuation value of silicon element is the difference between the highest and lowest relative percentage content of silicon atoms in the entire line scan.
[0082] Determination of the maximum particle size Dmax of silicon-based particles:
[0083] The negative electrode plate is cut vertically with an ion polisher, and more than 20 silicon-based particles are randomly selected from the plate under an electron microscope. The particle size of the silicon-based particles is tested, and the maximum particle size among the randomly selected particles is taken as Dmax.
[0084] Determination of fluoroethylene carbonate (FEC) content in electrolyte:
[0085] The lithium-ion battery is discharged to 0% state of charge (SOC) and then centrifuged. The liquid obtained after centrifugation is subjected to a GC-MS test to detect the mass content percentage of the FEC component in the electrolyte.
[0086] Lithium-ion battery room temperature cycle performance test:
[0087] The test temperature is 25°C. The lithium-ion battery is charged to 4.45V at a constant current of 0.7 times (C), then charged to 0.025C at a constant voltage, and discharged to 3.0V at 0.5C after standing for 5 minutes. The capacity obtained in this step is taken as the initial discharge capacity, and a cycle test of 0.7C charge / 0.5C discharge is performed for 400 cycles, and the discharge capacity of the 400th cycle is recorded. Cycle capacity retention rate = (discharge capacity of the 400th cycle / discharge capacity of the first cycle) × 100%.
[0088] Lithium-ion battery low temperature cycle performance test:
[0089] At 25°C, the formed lithium-ion battery was charged to 4.45V at a constant current of 0.2 times (C), then charged at a constant voltage until the current was less than or equal to 0.05C, then left to stand for 30 minutes, and then discharged to 3.0V at a constant current of 0.2C. The discharge capacity of the lithium-ion battery at 25°C and 0.2C was obtained by testing.
[0090] At 25°C, the lithium-ion battery was charged at a constant current of 0.2C to 4.45V, and then charged at a constant voltage to a current less than or equal to 0.05C; the battery cell was then placed in a -10°C environment, left to stand for 60 minutes, and then discharged at a constant current of 0.2C to 3.0V. The -10°C 0.2C rate discharge capacity of the lithium-ion battery was obtained by testing.
[0091] -10°C discharge capacity retention rate of lithium ion battery (%) = -10°C discharge capacity / 25°C discharge capacity×100%.
[0092] Lithium-ion battery expansion rate test:
[0093] At a test temperature of 25°C, a spiral micrometer is used to measure the thickness of the lithium-ion battery at 50% SOC, recorded as H0, and then the thickness of the lithium-ion battery is measured at 100% SOC when it is cycled to 400 cycles according to the steps in the cycle performance test, recorded as H1. 25°C cycle expansion rate = (H1-H0) / H0×100%.
[0094] Example 1-1
[0095] <Preparation of Silicon-based Composite Materials>
[0096] A porous carbon substrate with a Dmax of 25 μm is placed in a rotary kiln, the furnace tube is purged with nitrogen at room temperature for 30 minutes, and then the heating temperature of the porous carbon sample is increased to 450°C. The nitrogen flow rate is adjusted so that the gas residence time in the rotary kiln is at least 90 seconds, and maintained at this flow rate for 30 minutes. The gas supply is then switched from nitrogen to a mixed gas of silicon-containing gas (e.g., silane) and nitrogen, wherein the volume ratio of silicon-containing gas to nitrogen in the mixed gas is 5:95. After deposition for 8 hours at a gas flow rate of 200 sccm, nitrogen is continuously passed into the rotary kiln to blow out the silicon-containing gas from the kiln, and the rotary kiln is purged under nitrogen for 30 minutes, and then the rotary kiln is cooled to room temperature within several hours (e.g., 8 hours). Then, by switching the gas flow from nitrogen to air from a compressed air source, the nitrogen in the rotary kiln is gradually converted to air within 2 hours to obtain a silicon-based composite material, i.e., silicon-based particles. The difference B% between the maximum and minimum values of the relative percentage content of silicon atoms in the silicon-based particles is measured and is shown in Table 1.
[0097] <Preparation of negative electrode sheet>
[0098] The silicon-based composite material, graphite particles and nano-conductive carbon black prepared above are mixed in a mass ratio of 3:94:3 to obtain a first mixture; the first mixture and a binder polyacrylic acid (PAA) are added to deionized water in a mass ratio of 95:5 to prepare a slurry with a solid content of 70wt%, and the mixture is stirred evenly to obtain a first mixed slurry.
[0099] The first mixed slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, and dried under vacuum drying at 85°C for 12 hours to obtain a negative electrode sheet coated with negative electrode active material on one side; then, the above steps are repeated on the other surface of the negative electrode sheet to obtain a negative electrode sheet coated with negative electrode active material on both sides; then, the negative electrode sheet obtained above is cold pressed, striped, and cut to obtain a negative electrode sheet with a specification of 76mm×867mm. The thickness of the negative electrode sheet is 90mm, and the porosity is 33%.
[0100] <Preparation of positive electrode sheet>
[0101] The positive electrode active material lithium cobalt oxide, conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2.5:2.5, and NMP is added as a solvent to prepare a slurry with a solid content of 75wt%, and stirred evenly. The slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 90°C to obtain a positive electrode sheet with a coating thickness of 110μm. After the above steps are completed, the single-sided coating of the positive electrode sheet is completed. After that, the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet with a double-sided coating of positive electrode active materials. Then, after cold pressing and cutting, a positive electrode sheet with a specification of 74mm×851mm is obtained.
[0102] <Preparation of Electrolyte>
[0103] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) are uniformly mixed in a mass ratio of 1:1:1 as a base solvent, LiPF6 is added and stirred evenly to obtain an electrolyte, in which the mass percentage of LiPF6 is 12.5wt%.
[0104] <Preparation of Separator Film>
[0105] A polyethylene (PE) film with a thickness of 15 μm (provided by Celgard) was used.
[0106] <Preparation of lithium-ion batteries>
[0107] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is located between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, and after drying, the electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, formation, degassing, trimming, and other processes.
[0108] Example 1-2 to Example 1-14
[0109] Except for adjusting the strength A of the negative electrode current collector, the difference B% between the maximum and minimum relative percentage content of silicon atoms in the silicon-based particles, and the mass content C% of silicon elements in the negative electrode material layer as shown in Table 1, the rest is the same as Example 1-1.
[0110] Example 2-1 to Example 2-9
[0111] Except for adjusting the single-side thickness H of the negative electrode material layer and the maximum particle size Dmax of the silicon-based particles as shown in Table 2, the rest is the same as Example 1-6.
[0112] Example 3-1 to Example 3-9
[0113] Except for adjusting the porosity P% of the negative electrode plate and adjusting the mass content C% of silicon in the negative electrode material layer as shown in Table 3, the rest is the same as Example 2-3.
[0114] Example 4-1
[0115] Except for the fact that <Preparation of electrolyte> is different from Example 1-1, the rest is the same as Example 1-1.
[0116] <Preparation of Electrolyte>
[0117] In an argon atmosphere glove box with a water content of less than 10ppm, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) were uniformly mixed in a mass ratio of 1:1:1 as a base solvent, LiPF6 and fluoroethylene carbonate were added, and the mixture was stirred evenly to obtain an electrolyte, in which the mass percentage of LiPF6 was 12.5wt%, and the mass percentage of fluoroethylene carbonate was as shown in Table 4.
[0118] Example 4-2 to Example 4-4
[0119] Except for adjusting the mass percentage Q% of fluoroethylene carbonate as shown in Table 4, the rest is the same as Example 4-1.
[0120] Comparative Example 1-1 to Comparative Example 1-4
[0121] Except for adjusting the strength A of the negative electrode current collector, the difference B% between the maximum and minimum relative percentage content of silicon atoms in the silicon-based particles, and the mass content C% of silicon elements in the negative electrode material layer as shown in Table 1, the rest is the same as Example 1-1.
[0122] Table 1
[0123]
[0124]
[0125] It can be seen from Examples 1-1 to 1-14 and Comparative Examples 1-1 to 1-4 that when the strength A of the negative electrode current collector, the difference B% between the maximum and minimum values of the relative percentage content of silicon atoms in the silicon-based particles, and the mass content C% of silicon in the negative electrode material layer satisfy:
[0126] The cycling performance and expansion performance of lithium-ion batteries are improved.
[0127] Table 2
[0128]
[0129] The single-sided thickness H of the negative electrode material layer and the maximum particle size Dmax of the silicon-based particles will also affect the performance of the lithium-ion battery. It can be seen from Examples 1-6 and 2-1 to 2-9 that when H and Dmax satisfy H≥3×Dmax, the lithium-ion battery has good cycle performance and expansion performance.
[0130] Table 3
[0131]
[0132]
[0133] The porosity P% of the negative electrode sheet and the mass content C% of silicon in the negative electrode material layer will also affect the performance of the lithium-ion battery under the synergistic effect. It can be seen from Examples 2-3, 3-1 to 3-9 that when P and C meet: P>15×C 1 / 4 When the battery is heated, the lithium-ion battery has good room temperature cycle performance, expansion performance and low temperature cycle performance.
[0134] Table 4
[0135]
[0136] The mass content C% of silicon in the negative electrode material layer and the content Q% of fluoroethylene carbonate in the electrolyte will also affect the performance of the lithium-ion battery under synergistic effects. It can be seen from Examples 3-5, 4-1 and 4-4 that when Q and C satisfy: 0.3≤C / Q≤3, the lithium-ion battery has good room temperature cycle performance, expansion performance and low temperature cycle performance.
[0137] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. An electrochemical device, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer, in, The negative electrode material layer includes a silicon-based composite material, the silicon-based composite material includes silicon-based particles, the strength of the negative electrode current collector is A MPa, a line scan test is performed on the silicon-based composite material, and the difference between the maximum and minimum values of the silicon atomic percentage content in the silicon-based particles within the line scan test interval is B%, and the mass content of silicon element in the negative electrode material layer is C%, satisfying: A satisfies: 370≤A≤800; The C satisfies: 1≤C≤20; The electrolyte includes fluoroethylene carbonate. Based on the mass of the electrolyte, the mass percentage of the fluoroethylene carbonate is Q%, and Q and C satisfy: 0.3≤C / Q≤3.
2. The electrochemical device according to claim 1, wherein: The B satisfies: 10≤B≤16.
3. The electrochemical device according to claim 1, wherein The single-sided thickness of the negative electrode material layer is H, and the maximum particle size of the silicon-based particles is Dmax, satisfying: H≥3×Dmax.
4. The electrochemical device according to claim 3, wherein: The Dmax satisfies: 10 μm≤Dmax≤25 μm.
5. The electrochemical device according to claim 3, wherein: The H satisfies: 30 μm≤H≤90 μm.
6. The electrochemical device according to any one of claims 1 to 5, wherein: The porosity of the negative electrode sheet is P%, and P and C satisfy: P>15×C 1 / 4 .
7. The electrochemical device according to claim 6, wherein: The P satisfies: 18≤P≤40.
8. The electrochemical device according to any one of claims 1 to 5, wherein: The C satisfies: 1≤C≤10.
9. The electrochemical device according to any one of claims 1 to 5, wherein: The Q satisfies: 1≤Q≤20.
10. The electrochemical device according to any one of claims 1 to 5, wherein: The Q satisfies: 2≤Q≤10.
11. The electrochemical device according to any one of claims 1 to 5, wherein: The silicon-based particles include silicon and carbon, and the atomic ratio of silicon to carbon in the silicon-based particles is 1:1 to 2.
5.
12. An electronic device comprising the electrochemical device according to any one of claims 1 to 11.
Citation Information
Patent Citations
Preparation method of composite high-magnification silicon-based material, cathode material and lithium battery
CN105680023A
Negative electrode material for lithium secondary battery and negative electrode sheet manufactured of this
JP2007103382A
Lithium secondary battery
US20060068290A1